Dental implant placement with immersive technologies: A preliminary clinical report of augmented and mixed reality applications - Marcus, Engelschalk (2024)
A preliminary clinical report of implant placements with 2 immersive reality technologies is described: augmented reality with head mounted display and mixed reality with a tablet PC. Both immersive realities are promising and could facilitate innovative dental applications. However, mixed reality requires further development for clinical optimization.